Penyuluhan Tentang Makanan Pendamping Asi Dengan Status Gizi Balita - Masdarwati, Masdarwati; Kadir, Erni; Serli, Serli; Ruben, Sethiana Dewi; Pannyiwi, Rahmat; Rante, Anshar (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Health education is a health education activity, which is carried out by spreading messages, instilling beliefs, so that people are not only aware, know and understand, but are also willing and able to make recommendations related to health. Mother's Milk (ASI) is the best food for babies, so ASI plays a role in the baby's body's defense system to prevent various diseases, every drop of breast milk also contains minerals and enzymes to prevent disease and antibodies which are more effective compared to the content contained in milk formulas. The emergence of nutritional problems is multifactorial, therefore the approach and solution must be from several factors. The method of this activity is by lecturing which means a method of delivering health messages orally and accompanied by questions and answers and of course distributing leaflets to mothers and then counseling, evaluating activities, namely distributing pre-posttest questionnaires. The results of the increase were obtained by increasing the mother's knowledge about the nutritional status of the child.